Protein metabolism and urea kinetic in feedlot Nellore steers fed with different protein sources and inclusion levels - Souza, Vinícius Carneiro de [UNESP] (2020)
The use of rumen undegradable protein (RUP) sources in high-energy diets may be an alternative to increase the nitrogen use efficiency (NUE) in ruminants. In this study we had two main objectives: 1) to understand how the protein content of the diet and the rumen degradable protein (RDP) intake can affect urea recycling and its utilization. 2) how the protein content of the diet and the amino acid profile of the metabolizable protein (MP) can affect the efficiency of the use of amino acids (AA) in feedlot Nellore cattle receiving high-energy density diets. Thus, we evaluated the effects of different sources and protein levels in the diet of feedlot Nellore cattle receiving high-concentrate diets. We had two major hypotheses: 1) reducing dietary N associated with RUP sources can increase NUE by reducing ruminal NH3 concentration, urea production in the liver and urinary N excretion, while maintaining N available for microbial protein (MICP) synthesis through urea N recycling. 2) differences in AA use efficiency exists and the gross AA use efficiency is affected by dietary factors such as N sources and levels. These hypotheses were tested using six Nellore steers, cannulated in the rumen, duodenum and ileum with initial body weight (BW) of 354 ± 11.8 kg and 18 months of age. The animals were randomly assigned to receive each diet once over the 6 periods in a 6 × 6 Latin square design. Experimental diets consisted of 80% concentrate and 20% roughage (DM basis), where fresh chopped sugar cane was used as the roughage source and the concentrates differed in the protein source. Corn gluten meal (CGM) and dry distillers grains (DDG) were used as RUP sources, with low and intermediate ruminal degradability, respectively, and soybean meal and urea (SU) were used as RDP source. Treatments were arranged in a factorial A × B, where factor A consisted of 3 protein sources (PS; soybean meal plus urea, CGM and DDG) and factor B consisted of 2 dietary crude protein (CP) levels (PL; 11 and 14%). There was no interaction between PS and PL on nutrient intake and digestibility (P > 0.05). Animals fed diets with an inclusion level of 11% CP had greater (P < 0.05) non-fibrous carbohydrates (NFC) intake and tended (P < 0.10) to have greater intake of DM (% of BW and kg/day), organic matter (OM) and total digestible nutrients (TDN). Intake of RDP was greater (P < 0.05) and RUP intake was less (P < 0.05) when animals were fed SU diets. Animals fed DDG diets had greater (P < 0.05) NDF intake compared to SU or CGM diets. Animals fed DDG tended (P = 0.10) to have greater NDF apparent total-tract digestibility compared to those fed SU diets. Animals fed SU diets had a greater (P < 0.05) ruminal ammonia (NH3-N) concentration than those fed with CGM or DDG diets. Microbial N flow and efficiency was not affected (P > 0.05) by PL and PS. Animals fed SU diets had lower (P < 0.05) NUE and greater urea entry rate (UER). In addition, increasing PL from 11 to 14% CP tended (P < 0.10) to lead to greater UER production. Animals fed SU diets tended (P < 0.10) to have greater gastrointestinal entry rate (GER) than those fed CGM or DDG diets. Animals fed SU diets had greater (P < 0.05) urea N returned to ornithine cycle (ROC) compared to those fed CGM or DDG. When predicted by the equation developed by the Beef Cattle Nutrient Requirements Model (BCNRM) the amount of urea used for anabolism (UUA) was greater (P < 0.05) in animals fed 11% CP diets compared to those fed diets containing 14% CP. In addition, the predicted UUA was greater (P < 0.05) than the measured UUA. The ROC expressed as a proportion of UER was greater for diets with 11% CP than for those with 14% CP (P < 0.05). The urea N excreted in feces (UFE) as a proportion of GER tended (P < 0.10) to be greater for SU than for DDG and CGM. The proportion of MICP synthesis (% of total microbial N) from urea recycling was greater (P < 0.05) for animals fed CGM compared to those fed SU diets and also greater for diets with 11% CP than for those containing 14% CP. MICP synthesis from urea recycling expressed as a proportion of UER and GER, was greater for animals fed DDG. Animals fed diets containing 11% CP had higher MICP synthesis from urea recycling, when expressed as a proportion of UER, than did animals fed 14% CP diets (P < 0.05). There were no interactions between PS and PL for the flow of any AA evaluated (P > 0.05). The duodenal flow of essential (EAA) and non-essential AA (NEAA) was not affected (P > 0.05) by PS and PL. Proline concentration was increased in SU diets, reduced in CGM diets and not affected in DDG diets by the increase in PL. Diets containing DDG and 11% CP tended (P < 0.10) to have greater arginine and histidine concentration in rumen bacteria compared to SU and GGM diets with 11% CP; however, there was no difference between PS within the 14% CP level. Lysine concentration in rumen bacteria tended (P < 0.10) to be greater as the PL increased in the CGM diets. Tyrosine concentration in rumen bacteria tended (P < 0.10) to be greater in animals fed diets containing CGM compared to those fed DDG diets. Also, increasing PL in the diet from 11 to 14% CP tended (P < 0.10) to lead to higher concentrations of tyrosine in microbial protein. Animals fed DDG tended (P < 0.10) to have greater arginine, lysine and leucine supply from microbial protein than those fed diets containing SU or CGM. Animals fed DDG had greater (P < 0.05) NEAA supply from microbial protein flow than those fed diets containing SU, but they did not differ from animals fed CGM diets. Histidine and glutamate from microbial protein had a greater supply (P < 0.05) by the dietary inclusion of CGM or DDG compared to SU diets. Animals fed CGM or DDG tended (P < 0.10) to have greater proline and serine flow from microbial protein than those fed SU diets. Animals fed CGM or DDG tended (P < 0.10) to have greater EAA, arginine, isoleucine and valine supply from RUP fraction. The Leucine supply from RUP was greater (P < 0.05) in animals fed CGM or DDG compared to those fed SU diets. Plasma histidine concentration tended (P < 0.10) to be greater in animals fed DDG diets. Plasma leucine concentration was greater (P < 0.05) in animals fed CGM or DDG compared to those fed SU diets. Animals fed diets containing 14% CP had greater (P < 0.05) leucine concentration compared to the diets containing 11% CP. Plasma phenylalanine concentration was greater (P < 0.05) in animals fed diets containing CGM or DDG compared to those fed SU diets. Plasma valine concentration was greater (P < 0.05) in animals fed diets with a CP level of 14% compared to fed 11% CP diets. Plasma glutamine concentration was greater (P < 0.05) in animals fed SU diets compared to those fed CGM or DDG diets. Plasma glycine concentration was greater (P < 0.05) in animals fed SU diets compared to those fed CGM or DDG diets. There were interactions, or tendencies for interactions, between PS and PL for gross AA utilization of all AA evaluated, except methionine and cystine. Arginine and histidine utilization were greater in animals fed diets containing 11% CP with DDG and 14% CP with CGM. Animals fed the diet containing 11% CP and DDG showed greater isoleucine, lysine, phenylalanine, threonine, valine, alanine, aspartic, glutamate, proline, serine, and tyrosine use efficiency than other diets, except diet 14% CP with CGM which did not differ. Methionine and cystine utilization were not affected by PS or PL (P > 0.05). The AA use efficiency is affected by dietary protein levels and sources. Our results suggest that it is possible to increase the supply of essential AA using CGM or DDG (RUP sources) in the diet compared to soybean meal plus urea, especially in situations where it is possible to increase the microbial protein flow. Results from this study indicate that 11% of CP inclusion rate can be used for feedlot Nellore cattle fed high-concentrate diets without negatively affecting nutrient intake, digestibility and ruminal fermentation. Moreover, in the present experimental conditions, the tested RUP feed sources markedly increased NUE, while keeping the MICP synthesis constant by stimulating the use of recycled urea for microbial growth. In addition, the gross AA use efficiency is affected by dietary protein levels and sources.